The Impact of the Problem-Based Learning Model by Tri Kaya Parisudha on Primary School Students' Character - Wardhani, Ni Ketut Srie Kusuma; Mahendradhani, Gusti Ayu Agung Riesa; Wiradnyana, I Gede Arya (Yayasan Corolla Education Centre, 2024)
The purpose of this study is to assess the effects of integrating the Problem-Based Learning (PBL) model with Tri Kaya Parisudha (TKP) on the development of character traits such as positive thinking, politeness, compassion, and honesty in fifth-grade elementary school students. The research utilized a quasi-experimental design. This study involved fifth-grade students from elementary schools in Cluster VI, Kelurahan Kampung Baru, Buleleng District, spread across 6 elementary schools. Before selecting the sample, an equivalence analysis was conducted using one-way ANOVA, which showed that all the schools were equivalent. Two classes were randomly selected through a lottery as the sample. As a result, 32 students from SDN 5 Kampung Baru were designated as the experimental group, and 25 students from SDN 4 Kampung Baru were designated as the control group. Data collection was conducted via a questionnaire, and the analysis was carried out using both descriptive and inferential statistical methods (MANOVA). The results indicated that: (1) students who were taught using the PBL model combined with TKP exhibited higher levels of positive thinking, politeness, compassion, and honesty compared to those who were taught solely with the PBL model, and (2) there were significant differences in these character traits between the two groups. These findings suggest that the PBL model combined with TKP is more effective in fostering positive thinking, politeness, compassion, and honesty than the PBL model.